Does Treadmill Training Improve Balance Function of Healthy Untrained Young Adult Male? - Stephanie Theodora; Damayanti Tinduh; Rr. Indrayuni Lukitra Wardhani (Faculty of Medicine, Universitas Airlangga, 2019)
Background: Number of falls increase among elders and young adults prior to any cause. Occult balance disorder may become one of the morbidity factors that causes fall in young adults and eventually elders. One leg stance test reflects static balance function that might show occult balance disorder in healthy population. Closed eyes crossed arms one leg stance (CECAOLS) used to eliminate balance factors such as visual and arms sways that can elevate limit of stability (LOS). Treadmill used as a dynamic balance exercise with inclination and speed level as its’ component to challenge the balance function.Aim: to compare CECAOLS value in subjects with gradual increase of speed versus inclination in moderate intensity treadmill exercise.Methods: Nineteen healthy young adults male with sedentary lifestyle aged from 26 to 37 years old were recruited. Nine people in inclination group, ten people in speed group. Treadmill exercise with moderate intensity (70% maximal heart rate), exercise duration was 30 minutes (5 minutes warming up, 20 minutes core exercise, 5 minutes cooling down), 3 times/week, for 4 weeks. Measurement of CECAOLS value were done prior to first exercise and after completion of exercise in 4th week.Results: Significant increase of CECAOLS value at right leg inclination group with p=0.038. No significant increase of CECAOLS value in speed group (p>0.05).Conclusion: Moderate intensity treadmill exercise with gradual inclination increase 30 minutes duration, 3 times/week, for 4 week was proven to increase CECAOLS value in young adult healthy untrained male.